Good practice in social care: the views of people with severe and complex needs and those who support them. (3rd April 2014) - Gridley, Kate; Brooks, Jenni; Glendinning, Caroline
Abstract This paper reports findings drawn from a study of good practice in English social care for adults with disability and older people with severe and complex needs. People with severe and complex needs are a relatively small proportion of adult social care service users, but they are growing in numbers and have resource‐intensive needs. The study involved qualitative research with adults with disability and older people with severe and complex needs, family carers and members of specialist organisations (n = 67), focusing on the features of social care services they considered to be good practice. Data were collected between August 2010 and June 2011. The approach to data collection was flexible, to accommodate participants' communication needs and preferences, including face‐to‐face and telephone interviews, Talking Mats© sessions and a focus group. Data were managed using Framework and analysed thematically. Features of good practice were considered at three levels: (i) everyday support; (ii) service organisation; and (iii) commissioning. Findings relating to the first two of these are presented here. Participants emphasised the importance of person‐centred ways of working at all levels. Personalisation, as currently implemented in English social care, aims to shift power from professionals to service users through the allocation of personal budgets. This approach focuses very much on the role of the individual in directing his/her own support arrangements. However, participants in this study also stressed the importance of ongoing professional support, for example, from a specialist key worker or case manager to co‐ordinate diverse services and ensure good practice at an organisational level. The paper argues that, despite the recent move to shift power from professionals to service users, people with the most complex needs still value support from professionals and appropriate organisational support. Without these, they risk being excluded from the benefits that personalisation, properly supported, could yield.